COMPARISON OF EFFECTS OF SITAGLIPTIN AND A COMBINATION OF NALTREXONE AND BUPROPION IN HIGH FAT DIET-INDUCED OBESITY MODEL IN RATS - KULMI, MOHIT; SAXENA, GAURAV (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The study aimed to compare the anti-obesity effect of Sitagliptin and a combination of Naltrexone and Bupropion in high-fat diet-induced obesity model in animals. Methods: This study was a prospective study of 17 weeks duration. Obesity was induced in rats by feeding them a high-fat diet over a period of 17 weeks. Sitagliptin and a combination of Naltrexone and Bupropion were administered to two groups for 5 weeks and various parameters such as body weight, blood glucose, food intake, and BMI were measured and analyzed over a period of 5 weeks. Results: In this study, on administration of Sitagliptin and a combination of Naltrexone and Bupropion, there was a gradual weight loss in rats. The combination of Naltrexone and Bupropion showed a significant (p<0.05) effect on reduction in body weight, reduction in food intake, and reduction of BMI in obese rats, whereas Sitagliptin showed a significant reduction in blood glucose in rats. Conclusion: In the present study combination of Naltrexone and Bupropion stood most effective in reducing weight, food intake, as well as BMI.